Exploratory data analysis with MATLAB - Martinez, Wendy L.; Martinez, Angel R.; Solka, Jeffrey (Series in computer science and data analysis., 2017)
Exploratory Data Analysis with MATLAB, Third Edition presents EDA methods from a computational perspective and uses numerous examples and applications to show how the methods are used in practice. The authors use MATLAB code, pseudo-code, and algorithm descriptions to illustrate the concepts. The MATLAB code for examples, data sets, and the EDA Toolbox are available for download on the book's website. --